Breeding profiles at the periparturient stage in captive red foxes (Vulpes vulpes) mating naturally or subjected to artificial insemination in Japan - Yatu Minoru (Journal of Veterinary Research, 2019)
Introduction: Breeding profiles at the periparturient stage in red foxes which mated naturally or were subjected to artificial insemination were retrospectively surveyed using 130 vixens during their reproductive seasons of 2012–2017 in Japan. Material and Methods: Natural mating vixens were encouraged a maximum of three times with the same male, while artificial insemination was conducted using frozen-thawed semen with the bovine semen extender as a diluent. Results: With natural mating, conception rates after one, two, and three copulations were 55.8%, 68.0%, and 85.7%, respectively, showing a significant difference between the rates for one and three copulations. Conception rates with artificial insemination were 82.4%. Mean gestation periods were between 52.1 and 53.3 days in all groups. Mean litter sizes were 3.7–4.3 cubs with natural mating, and 4.4 cubs with artificial insemination. Although some sporadic and inconsistent changes in litter sizes were noted between primiparous and multiparous groups, these were of doubtful clinical importance. Conclusion: This is the first report from Japan concerning basic breeding events of red fox vixens in captivity.